Lesson Study to Improve Students' Scientific Literacy Abilities on Respiratory System Material - Lesy Luzyawati; Idah Hamidah; Aditya Fauzan; Erti Wiyati (Postgraduate, University of Mataram, 2023)
Less varied learning method result in low scientific literacy of students. This study aims to determine whether the application of lesson study in learning can improve students' scientific literacy skills in the Respiratory System material. This research is action research carried out at SMA Negeri 1 Lohbener. The subjects in this study were students of class XI IPA 1 with a total sample of 22 people. The instrument used in this study was HOTs-based literacy question sheets which were given in each cycle to measure students' scientific literacy improvement. The results of data processing obtained an average score of scientific literacy skills in cycle I of 53.0 with a percentage of 53% and in the very low category, the average score in cycle II of 57.0 with a percentage of 57% and in the low category, and the average score in cycle III of 67.0 with a percentage of 67% and in the moderate category. The main factor causing an increase in students' scientific literacy skills only reaching the moderate category was students who were not used to answering HOTs-based literacy questions and were used to answering LOTs-type questions, so they experienced difficulties in doing the formative tests given. Even so, the application of lesson study in learning material on the respiratory system is proven to be able to improve students' scientific literacy skills at each level. Based on the results of observations of teachers and students during the implementation of cycle actions, it appears that the implementation of actions has reached the predetermined performance indicators